Pemuridan Pria Sejati Bandung: Upaya Pemulihan Spiritualitas dan Kepemimpinan Pria dalam Keluarga Kristen - Darmawan, Darmawan; Benjamin, Theophilus (Indonesia Christian Religion Theologians Association and Widya Agape School of Theology, 2025)
The crisis of fatherhood and the weakening of male leadership within families have become key factors contributing to the dysfunction of Christian households in Indonesia. Through the True Men Bandung Discipleship Program, this community service initiative aims to restore men’s spirituality and leadership responsibility in accordance with biblical principles. The program was conducted through a two-day discipleship camp followed by continuous mentoring using the 4M method (praying, reading, reflecting, and sharing). The results indicate a significant improvement in participants’ spiritual commitment, the restoration of marital relationships, and the strengthening of male involvement in family leadership roles. This project demonstrates that discipleship can serve as an effective model of faith-based community service that fosters family resilience and spiritual transformation within the church community.